2020
DOI: 10.1093/medlaw/fwaa020
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Disagreement: A Multi-Jurisdictional Comparative Analysis of Disputes About Children’s Medical Care

Abstract: Recently, the English courts have dealt with a number high-profile, emotive disputes over the care of very ill children, including Charlie Gard, Alfie Evans, and Tafida Raqeeb. It is perhaps fair to say such cases have become a regular feature of the courts in England. But is the situation similar in other jurisdictions? If not, are there lessons to be learned from these jurisdictions that do not seem to need to call on judges to resolve these otherwise intractable disputes? We argue that many of the differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…While we have not looked at the legal context beyond this jurisdiction, there is certainly scope to consider whether mediation would be effective in other legal cultures, particularly those where informal resolution and reluctance to use the courts is already more embedded. 4,51 We have shown that the law is complex and does not effectively deal with the role of mediation as an alternative way of resolving these difficult cases. However, we do have emerging evidence about the benefits of mediation in cases concerning adults in the CoP as well as benefits from other areas of practice such as SEND.…”
Section: Discussionmentioning
confidence: 99%
“…While we have not looked at the legal context beyond this jurisdiction, there is certainly scope to consider whether mediation would be effective in other legal cultures, particularly those where informal resolution and reluctance to use the courts is already more embedded. 4,51 We have shown that the law is complex and does not effectively deal with the role of mediation as an alternative way of resolving these difficult cases. However, we do have emerging evidence about the benefits of mediation in cases concerning adults in the CoP as well as benefits from other areas of practice such as SEND.…”
Section: Discussionmentioning
confidence: 99%
“…52 Although democracy permits different values and beliefs of parents that may influence their position, clinicians must be committed to focussing on the needs of the child with life-limiting disease. 54 By acknowledging suffering and futility in the context of autonomy, there is significance in recognising the limitations of the relational autonomy of parents.…”
Section: Application Of the Four Principlesmentioning
confidence: 99%
“…While the value of applying to the court lies in the resolution of an otherwise intractable conflict, litigation does have disadvantages such as the length of time before a final conclusion is reached,3 the financial costs4 and the adverse effects of an adversarial process on the relationship between parents and clinicians 5. It is not surprising therefore that especially after highly contentious cases questions are asked how to avoid such litigation in future 6 7…”
Section: Introductionmentioning
confidence: 99%